Sidewalk accessibility at Melaka's traditional streets for people with disabilities (PwDs) - Ja'afar, Nor Haslina; Abdul Rahim, Asiah; Abd Samad, Nur Amirah; Che Rahim, Che Raiskandar (Malaysian Institute of Planners, 2017)
The accessibility of street as a social arena that fulfils the need for people with disabilities (PwDs) is an important consideration in the urban design of an area. With the rising number of PwDs in Malaysia, this aspect of street design is even more critical. This paper evaluates the accessibility level of sidewalk along Jalan Hang Jebat, Melaka to PwDs. On-site access audit simulation was carried out. Actual PwDs were engaged for the simulation. It was found that the sidewalk in inaccessible to PwDs due to presence of barriers and thedesign of the sidewalk itself. This papersuggest that the minimum requirement of MS1184:2014 must be implemented in the sidewalk design and the concept of ‘shared space’ can be adopted in the study area.